ANALISIS MEKANISME PERTAHANAN DIRI PADA PESERTA DIDIK KELAS XI SMA ISLAM BAWARI PONTIANAK TAHUN 2023 - Jailani, Muhammad; Wicaksono, Luhur; Yuline, Yuline (Universitas Tanjungpura, 2024)
This research aims to determine the self-defense mechanisms of class XI students at Bawari Islamic High School, Pontianak. The problem in this research is what is the self-defense mechanism for Class XI students at BAWARI Islamic High School, Pontianak. The aim of this research is to describe the self-defense mechanisms of class XI students at BAWARI Islamic High School Pontianak. The method used in this research is a descriptive method and the form of this research is a survey study. The sample for this research was 30 students in class XI. The technique in this research uses indirect communication techniques using data collection tools in the form of questionnaires. The data analysis technique in this research is to use a percentage calculation formula. The results of this research are self-protection mechanisms for class %